Evaluation of inhibitory effect of self-etch adhesives incorporated with proanthocyanidin on cysteine cathepsins present in dentin hybrid layer using gelatin zymography: An In vitro study - Arun Senthamilselvan; Kaarunya Ravikumar; D Y Mallikarjunan; Thendral Annadurai; Mothiraj Samynathan; R Jeya Varshini (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study is to evaluate the inhibitory effect of single-bottle and two-bottle self-etch adhesive system after surface pretreatment with 6.5% proanthocyanidin (PA) on cysteine cathepsins (CCs) present in dentin hybrid layer using gelatin zymography. Materials and Methods: Thirty-five samples of dentin measuring 3 mm × 3 mm were obtained from 35 caries-free human third molars which were divided into seven groups. The bonded specimens were cut vertically into 1 mm thick adhesive/dentin interfaces with microtome and were pulverized into powder and subjected to zymography analysis for enzymatic activity. Results: Group VI and VII which were positive control groups had shown thicker clear bands of 50 kDa. Group IV and V which had the administration of chlorhexidine showed thicker clear bands of 50 kDa which indicated slight activity of CCs. Group II in which PA used along with single-bottle system also showed thicker clear band of 59 kDa. CCs could be active due to strong acidic nature of monomer in this group. Group III in which PA used along with two bottle system had no band formation where there is crosslinking of catalytic and allosteric domains of enzymes by PA. Conclusion: Under the limitations of this study, PA proved as a non-specific natural inhibitor of CCs. Two-bottle system showed inhibition of CCs and single bottle system failed to inhibit their activity. Future research have to be done on the bond strength and durability of self-etch adhesives after using PA and its effect on long term survival of the restorations.